Brief notes on equality issues - Proto Pisani, Andrea (2016)
It is necessary put aside the idea that infinite economic development is the solution to terminate inequalities that exist in the world. Should consider a new model of society, which look for specify in the reality the value of justice, the hand of principles of equality and fraternity, where man is in a world of cooperation with others.